Can we throw information out of visual working memory and does this leave informational residue in long-term memory? - Maxcey, Ashleigh M.; Woodman, Geoffrey F. (Frontiers in Psychology, 2014)
Can we entirely erase a temporary memory representation from mind? This question has been addressed in several recent studies that tested the specific hypothesis that a representation can be erased from visual working memory based on a cue that indicated that the representation was no longer necessary for the task. In addition to behavioral results that are consistent with the idea that we can throw information out of visual working memory, recent neurophysiological recordings support this proposal. However, given the infinite capacity of long-term memory, it is unclear whether throwing a representation out of visual working memory really removes its effects on memory entirely. In this paper we advocate for an approach that examines our ability to erase memory representations from working memory, as well as possible traces that those erased representations leave in long-term memory.